Iosif Hadjikyriako and Mia Gaia Trentin (eds). Cypriot cultural details: proceedings of the 10th Annual Meeting of Young Researchers in Cypriot Archaeology - Charalambos, Paraskeva (Journal of Greek Archaeology, 2016)
Arguably the archaeology of Cyprus has in the past few decades grown to a subdiscipline of archaeology in its own right. Today, a new generation of researchers boldly extend the frontiers of Cypriot archaeology, as it seeks to explore different themes, pose novel questions and challenge longstanding views. The edited volume under review contains a total of 12 papers delivered by young researchers in the course of the 10th annual conference in Postgraduate Cypriot Archaeology (PoCA) held at the Ca’ Foscari University of Venice in 2010. Accordingly, the papers are the product of ongoing or recently concluded postgraduate, mostly doctoral, studies; they present novel approaches methodologically and theoretically, and exhibit a high degree of innovative thought. Spatially the papers focus on the island of Cyprus and sometimes broaden their view to include the Eastern Mediterranean and Aegean cultural areas, while with regard to temporality they range from the Early Bronze Age to the 18th century AD. In terms of format the volume commences with a brief introduction by the editors followed by four sections encompassing select sets of issues, which are henceforth critically explored.